2020
DOI: 10.1177/1533033820948054
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Promotes the Proliferation and Metastasis of Lung Cancer by Activating the Wnt/β-Catenin Pathway

Abstract: The aim of this study was to investigate the role of high mobility group protein-1 (HMGB1) in the proliferation and migration of lung cancer cells. CCK-8 assays and colony formation assays were used to evaluate the effect of HMGB1 regulation on cancer cell viability and colony formation. Trans-well assays and wound healing assays were also performed. Our data showed that HMGB1 is upregulated in clinical lung cancer tissues compared with non-cancer tissues, and it is differentially expressed in lung cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In recent years, many studies have focused on its role in a variety of cancers, including CRC. Various reports have shown that HMGB1 expression is significantly upregulated in breast cancer, gastric cancer, lung cancer and other cancers and downregulated in pancreatic cancer [ 27 30 ]. Researchers have reported that HMGB1 may regulate the reactivity of rectal cancer cells to preoperative chemoradiotherapy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have focused on its role in a variety of cancers, including CRC. Various reports have shown that HMGB1 expression is significantly upregulated in breast cancer, gastric cancer, lung cancer and other cancers and downregulated in pancreatic cancer [ 27 30 ]. Researchers have reported that HMGB1 may regulate the reactivity of rectal cancer cells to preoperative chemoradiotherapy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 has been shown to be involved in inflammatory and oxidative stress and apoptosis through multiple signaling pathways including WNT, Keap1/Nrf2/ARE, and PI3K/AKT [ 36 38 ]. Furthermore, previous studies have confirmed the role of the ROS/NF- κ B pathway in activating HMGB1 in TDI-induced inflammatory injury [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet HMGB1 has been implicated in thrombosis, inflammation, and platelet activation involving TLR4/RAGE [ 39 , 41 ]. Tumor HMGB1 and TLR4/RAGE receptors promote cell proliferation, survival, migration, epithelial-to-mesenchymal transition, and apoptosis resistance involving interaction with β-catenin, Runx2, YAP1, and TGF-β1/Smad [ 38 , 42 , 43 , 44 , 45 , 46 ]. However, HMGB1 released from dying tumor cells may stimulate bone marrow-derived tumor-infiltrating myeloid dendritic cells through HMGB1/TLR2 signaling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%